Coronavirus disease 2019 in patients with chronic immune thrombocytopenia on thrombopoietin receptor agonists: new perspectives and old challenges. Issue 1 (January 2022) - Pantic, Nikola; Suvajdzic-Vukovic, Nada; Virijevic, Marijana; Pravdic, Zlatko; Sabljic, Nikica; Adzic-Vukicevic, Tatjana; Mitrovic, Mirjana
Abstract : N/A: There are limited data on the impact of severe acute respiratory syndrome corona virus 2 infection in patients previously diagnosed with primary immune thrombocytopenia (ITP) on thrombopoietin receptor agonist therapy (TPO-RA). Seven chronic ITP patients who had contracted COVID-19 and had been treated with TPO-RA are included in the study. Demographic, ITP treatment and comorbidities data were collected retrospectively from patients' medical records. Data regarding clinical course of COVID-19 were collected prospectively. During the infection, all patients had platelet count higher than average, and platelet count peak was mainly observed on day 7. For that reason, therapy modification was required. However, platelet count increment was transient in most ITP patients. One patient developed pulmonary embolism despite the use of therapeutic dose of anticoagulants. One patient died of respiratory failure whereas another developed rebound thrombocytopenia after the infection and consequential intracerebral hemorrhage. Careful platelet count monitoring and therapy management are needed in chronic ITP patients on TPO-RAs with COVID-19.